Mycobacterium tuberculosis-stimulated whole blood culture to detect host biosignatures for tuberculosis treatment response. (May 2021) - Cilliers, Karen; Menezes, Angela; Webber, Tariq; Dockrell, Hazel M.; Cliff, Jacqueline M.; Kleynhans, Léanie; Chegou, Novel N.; du Plessis, Nelita; Loxton, André G.; Kidd, Martin; Djoba Siawaya, Joel Fleury; Ronacher, Katharina; et al.
Abstract: Host markers to monitor the response to tuberculosis (TB) therapy hold some promise. We evaluated the changes in concentration of Mycobacterium tuberculosis (M.tb)-induced soluble biomarkers during early treatment for predicting short- and long-term treatment outcomes. Whole blood samples from 30 cured and 12 relapsed TB patients from diagnosis, week 1, 2, and 4 of treatment were cultured in the presence of live M.tb for seven days and patients followed up for 24 weeks after the end of treatment. 57 markers were measured in unstimulated and antigen-stimulated culture supernatants using Luminex assays. Top performing multi-variable models at diagnosis using unstimulated values predicted outcome at 24 months after treatment completion with a sensitivity of 75.0% (95% CI, 42.8–94.5%) and specificity of 72.4% (95% CI, 52.8–87.3%) in leave-one-out cross validation. Month two treatment responder classification was correctly predicted with a sensitivity of 79.2% (95% CI, 57.8–92.9%) and specificity of 92.3% (95% CI, 64.0–99.8%). This study provides evidence of the early M.tb-specific treatment response in TB patients but shows that the observed unstimulated marker models are not outperformed by stimulated marker models. Performance of unstimulated predictive host marker signatures is promising and requires validation in larger studies. Highlights : Mycobacterium tuberculosis -specific response in early TB treatment. Stimulated marker models do not outperform unstimulated marker models. Performance of predictive host marker signatures is promising.